2011
DOI: 10.3151/jact.9.31
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrochemical Penetration of Lithium Ions on Concrete Expansion Due to ASR

Abstract: Concrete expansion due to alkali-silica reaction (ASR) is one of the serious deterioration mechanisms of concrete structures. However, no promising repair method for ASR has been established yet. In a bid to remedy this situation, an electrochemical technique to accelerate the penetration of the lithium ions (Li + ) in a lithium-based electrolyte solution into concrete has been developed for the purpose of suppressing ASR-induced expansion due to Li + . From the results of past research work, the penetration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, application of these special chemical admixtures remains very limited until now, probably because of the high cost. Lithium treatment of ASR-affected existing structures in order to stop ongoing ASR has also been investigated (Ueda et al 2011), but this is beyond the scope of this textbook.…”
Section: Mitigationmentioning
confidence: 99%
“…However, application of these special chemical admixtures remains very limited until now, probably because of the high cost. Lithium treatment of ASR-affected existing structures in order to stop ongoing ASR has also been investigated (Ueda et al 2011), but this is beyond the scope of this textbook.…”
Section: Mitigationmentioning
confidence: 99%
“…For reducing such risk, electrochemical introduction of lithium ions by using lithium-based electrolyte solution has been investigated (Ashida et al 1999;Whitemore and Abbott 2000) expecting the effect of suppressing ASR-induced expansion of concrete (MacCoy and Caldwell 1951;Diamond and Ong 1992;Lumley 1997). Past investigations (Souza et al 2017;Ueda et al 2005Ueda et al , 2006Ueda et al , 2011Folliard et al 2008) found that the ASR-induced expansion of concrete after the electrochemical treatment tended to be suppressed compared with the non-treated case mainly around the exposed surface.…”
Section: Introductionmentioning
confidence: 99%